Resolution No. 18- Graduated Income Tax (Tufts Archival Research Center, 2007)
Massachusetts AFL-CIO resolutions on graduated income tax, excise taxes, and the support privacy act. Supports a graduated income tax in Massachusetts. Opposes regressive excise taxes and hiring discrimination based on off the job activities.